Cargo Manifest Forgery by Shipping Administration Officers under Indonesian Criminal and Shipping Law - Zulfan Noor Mahazalien; Noenik Soekorini; Hartoyo Hartoyo; Fitri Ayuningtyas; Siti Marwiyah (JURNAL HUKUM SEHASEN, 2026)
This study examines the criminal liability of shipping administrative officers (krani) involved in the forgery of shipping documents without physical verification. The analysis refers to Article 263 of the Indonesian Criminal Code and Law No. 17 of 2008 on Shipping. It focuses on the dual role of the krani as both a technical executor and a subject of criminal liability, as illustrated in District Court Decision No. 323/Pid.Sus/2017/PT.DKI. Employing a normative legal method with statutory, conceptual, and comparative approaches, the study draws upon statutory provisions, legal doctrines, and relevant jurisprudence. Findings indicate that shipping officers hold a crucial legal position within corporate responsibility chains. However, the regulatory framework lacks explicit boundaries regarding their authority and liability. The court concluded that the defendant had actively prepared and signed falsified documents without conducting proper verification, fulfilling the elements of criminal offense. Nevertheless, assigning criminal blame solely to lower-level officers may risk abuse of hierarchical power and allow impunity for supervisory officials. The study underscores the need for clearer legal norms delineating criminal responsibility between administrative personnel, superiors, and corporate entities. It recommends strengthening internal controls and implementing continuous compliance training to prevent the unjust criminalization of technical staff lacking substantive decision-making authority.